2015
DOI: 10.1016/j.jvir.2014.12.489
|View full text |Cite
|
Sign up to set email alerts
|

A new angiographic imaging platform reduces radiation exposure for patients with liver cancer treated with transarterial chemoembolization

Abstract: Objectives To quantify the reduction of radiation liver cancer patients are exposed to during transarterial chemoembolization (TACE), while maintaining diagnostic image quality, using a new C-arm imaging platform. Methods In this prospective, HIPAA-compliant, IRB-approved, two-arm trial, 78 consecutive patients with primary or secondary liver cancer were treated with TACE on a C-arm imaging platform before and after an upgrade incorporating optimized acquisition parameters and advanced real-time image processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Radiation dose caused by scattered x-rays during conventional angiography remains an unsolved problem addressed by numerous investigations [10,11,24]. In our study, we showed that by means of 4D-CTA, a large part of conventional angiography leading to increased radiation exposure for the radiologist during TACE may be evitable, as dose-area-product and thus, scattered radiation could be reduced by half compared to traditional TACE.…”
Section: Discussionmentioning
confidence: 60%
“…Radiation dose caused by scattered x-rays during conventional angiography remains an unsolved problem addressed by numerous investigations [10,11,24]. In our study, we showed that by means of 4D-CTA, a large part of conventional angiography leading to increased radiation exposure for the radiologist during TACE may be evitable, as dose-area-product and thus, scattered radiation could be reduced by half compared to traditional TACE.…”
Section: Discussionmentioning
confidence: 60%